2019
DOI: 10.1097/pr9.0000000000000761
|View full text |Cite
|
Sign up to set email alerts
|

Functional and histological improvements of small nerve neuropathy after high-concentration capsaicin patch application: A case study

Abstract: Introduction: Small fiber neuropathy has been found to occur in a large variety of pathological onditions, and the gold standard for diagnosis of small fiber neuropathy is skin biopsy. Sudorimetry is now considered an accurate technique to evaluate small fiber function with a good sensitivity and specificity for the diagnosis of small fiber neuropathy. Capsaicin high-concentration patch is approved for the treatment of peripheral neuropathic pain in adults either alone or in combination with other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…showed that the sensitivity of COMPASS‐31 to detect AN increased from 59% to 85% when combined with fESC. In addition, ESC measures were found to correlate with the intraepidermal density of small nerve fibres on skin biopsy 26,30,32,33 . Thus, ESC assessment in ATTRwt‐CA patients should improve the management of these patients to prevent the deleterious impact of dysautonomia on cardiomyopathic morbidity and mortality 18 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…showed that the sensitivity of COMPASS‐31 to detect AN increased from 59% to 85% when combined with fESC. In addition, ESC measures were found to correlate with the intraepidermal density of small nerve fibres on skin biopsy 26,30,32,33 . Thus, ESC assessment in ATTRwt‐CA patients should improve the management of these patients to prevent the deleterious impact of dysautonomia on cardiomyopathic morbidity and mortality 18 …”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that the use and value of ESC measurement should be extended to ATTRwt-CA as well. In addition, ESC measurement can serve to follow the course of distal AN and its treatment, as previously shown in neuropathy associated with ATTRv, 10,30 chemotherapy, 26,27 or bariatric surgery. 28 The present study is the first to demonstrate an association between fESC reduction and a poor functional prognosis (cardiac decompensation and death).…”
Section: Prevalence Of Autonomic Neuropathy In Transthyretin Wild-typmentioning
confidence: 93%
See 1 more Smart Citation